PENYELESAIAN PROGRAM LINIER MENGGUNAKAN METODE SIMPLEKS DUA FASE DAN METODE QUICK SIMPLEKS DUA FASE - Elfira - Safitri; Sri - Basriati; Mohammad - Soleh; Yuhandi - - (Universitas Pendidikan Ganesha, 2021)
Mitra Pekanbaru Clothing shoots is one of a shop engaged in convection. In this case, Mitra Pekanbaru Clothing produces 4 types of uniforms, namely female Madrasah Aliyah uniform, male Madrasah Aliyah uniform, female Madrasah Ibtidaiyah uniform, and male Madrasah Ibtidaiyah uniform. Mitra Pekanbaru Clothing shoots to achieve maximum profit, so it needs optimization.The method used in this research is the two-phase simplex method and the two-phase quick simplex method. The purpose of this study is to determine the completion of a linear programming using the two-phase simplex method and the two-phase quick simplex method to obtain an optimum and feasible solution. The two-phase method of taking leaving variables and entering variables takes one positive variable, while the quick simplex method can be taken simultaneously with more than one negative value.Based on the research results, it was found that the completion of the linear programming using the two-phase quick simplex method was more efficient than the two-phase simplex method. This can be seen from the number of iterations performed, the two-phase method performs iterations four iteration and the two-phase quick simplex method performs one iteration. The two-phase simplex method and two-phase quick simplex yield the same values. So it can be concluded that that Mitra Pekanbaru Clothing has to produce 15 units of female Madrasah Aliyah uniform, 20 units of male Madrasah Aliyah uniform, 15 units of female Madrsah Ibtidaiyah uniform, and 20 units of male Madrasah Ibtidaiyah uniform, with a maximum profit of Rp.5.600.000.- Mitra Pekanbaru Clothing shoots is one of a shop engaged in convection. In this case, Mitra Pekanbaru Clothing produces 4 types of uniforms, namely female Madrasah Aliyah uniform, male Madrasah Aliyah uniform, female Madrasah Ibtidaiyah uniform, and male Madrasah Ibtidaiyah uniform. Mitra Pekanbaru Clothing shoots to achieve maximum profit, so it needs optimization. The method used in this research is the two-phase simplex method and the two-phase quick simplex method. The purpose of this study is to determine the completion of a linear programming using the two-phase simplex method and the two-phase quick simplex method to obtain an optimum and feasible solution. The two-phase method of taking leaving variables and entering variables takes one positive variable, while the quick simplex method can be taken simultaneously with more than one negative value. Based on the research results, it was found that the completion of the linear programming using the two-phase quick simplex method was more efficient than the two-phase simplex method. This can be seen from the number of iterations performed, the two-phase method performs iterations four iteration and the two-phase quick simplex method performs one iteration. The two-phase simplex method and two-phase quick simplex yield the same values. So it can be concluded that that Mitra Pekanbaru Clothing has to produce 15 units of female Madrasah Aliyah uniform, 20 units of male Madrasah Aliyah uniform, 15 units of female Madrsah Ibtidaiyah uniform, and 20 units of male Madrasah Ibtidaiyah uniform, with a maximum profit of Rp.5.600.000.-